Influence of dry, extruded-expelled soybean meal from different manufacturers on growth performance of nursery pigs - J C Woodworth; M U Steidinger; Joel M DeRouchey; Michael D Tokach; Jim L Nelssen; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 2000)
A total of 150 pigs (initially 22 lb; 42 d of age) was used to determine the influence of dry, extruded-expelled soybean meal from three different manufacturers on growth performance of pigs. No differences were observed for ADG, ADFI, or F/G between any of the sources. All three sources resulted in performance similar to that with a cornsoybean meal diet with added fat. These results confirm the accuracy of the energy values published in the 1998 Swine Day Report for dry, extruded-expelled soybean meal.; Swine Day, Manhattan, KS, November 16, 2000
Keywords: Swine day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-138-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 858; Swine; Nursery pigs; Growth; Soybean meal; Processing